2015
DOI: 10.1099/ijsem.0.000659
|View full text |Cite
|
Sign up to set email alerts
|

Marinobacter confluentis sp. nov., a lipolytic bacterium isolated from a junction between the ocean and a freshwater lake

Abstract: A Gram-stain-negative, motile, aerobic and rod-shaped bacterium, designated HJM-18T, was isolated from the place where the ocean and a freshwater lake meet at Hwajinpo, South Korea, and subjected to a taxonomic study using a polyphasic approach. Strain HJM-18T grew optimally at 30 °C, at pH 7.0–8.0 and in the presence of 1.0–3.0 % (w/v) NaCl. Phylogenetic trees based on 16S rRNA gene sequences showed that strain HJM-18T belonged to the genus Marinobacter. Strain HJM-18T exhibited 16S rRNA gene sequence similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…2). Previous studies demonstrated a positive lipolytic activity of Marinobacter confluentis , which was isolated from the junction between fresh water and marine water [50, 52]. In our study, the bacterial strain grown in a liquid culture medium and a significant lipolytic activity −2.105 nkatml −1 was detected in the supernatant.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…2). Previous studies demonstrated a positive lipolytic activity of Marinobacter confluentis , which was isolated from the junction between fresh water and marine water [50, 52]. In our study, the bacterial strain grown in a liquid culture medium and a significant lipolytic activity −2.105 nkatml −1 was detected in the supernatant.…”
Section: Resultssupporting
confidence: 57%
“…In previous reports, a bacterial strain of Aneurinibacillu s sp. has shown a significant variable activity in different screening methods on different media supplemented with olive oil as a carbon source [52].…”
Section: Resultsmentioning
confidence: 99%
“…confluentis KCTC 42705 T or M. halotolerans CP12 T [41, 42]. The sole respiratory quinone of strain JB02H27 T was ubiquinone-9 (Q-9, 100 % determined by HPLC), consistent with the other members of the genus Marinobacter [41–43].…”
Section: Full-textmentioning
confidence: 78%
“…We observed a significantly higher abundance of phosphatidylglycerol lysyltransferase (mprF) genes in cryopeg communities, used by bacteria to alter the net charge of their cellular envelope and resist a variety of cationic antimicrobials (Ernst et al, 2009), as well as for osmoprotection (Dare et al, 2014). As phosphatidylglycerol is a major building block of Marinobacter membranes (Park et al, 2015;Zhong et al, 2015), FIGURE 6 | Schematic of genomic adaptations to life in subzero hypersaline sea-ice brines (upper panels) and cryopeg brines (lower panels). Sea ice, exposed to atmospheric conditions and in exchange with underlying seawater (left), is characterized by vertical gradients in temperature, salinity and nutrient availability and subject to temporal disturbances of these conditions.…”
Section: Elaborate Competitive Strategies At High Cell Densities In Subzero Brinesmentioning
confidence: 99%